Forage legumes and grasses: more advantages in pure crop rotation or intercropping? - Vargiu M.; Spanu E.; Mulè P. (Forage resources and ecosystem services provided by Mountain and Mediterranean grasslands and rangelands, 2014)
Intercropping of grasses and legumes could represent a viable alternative to rotation because of the ready availability of nitrogen and the complementary distribution of the aerial and root systems. This paper reports two years (2012-2013) forage yield results of some legumes (berseem and squarrose clover, hairy vetch and burr medic) and grasses (ryegrass and oats) grown as pure crops as well as intercrops. In the two years the annual dry matter production was 5 t ha-1 but seasonal yield was very different for each species due to inter-annual weather variability. In the second year, except for vetch, that showed a rather stable production, forage yield was delayed increasing hay production. In the first year, total yield of intercropping (except for ryegrass/clover mixture) was often higher than pure crop (Land Equivalent Ratio >1). Seasonal production was instead variable: the mixtures berseem/grass, medic/grass and squarrose/oats for pasture, vetch/grass and squarrose/oats for hay were more favourable than pure crops. In the second year, mixtures was less convenient (LER<1); benefits were evidenced in some case (medic/grasses, berseem/oats and squarrose/oats) only for hay.
Joint Meeting of the "Mountain Pastures, Mediterranean Forage Resources (FAO/ESCORENA-CIHEAM) and Mountain Cheese" Network, 2014/06/24-26, Clermont-Ferrand (France)